The occurrences of ultramafic pegmatites at Dwarsrivier Mine, Lower Critical Zone, Eastern Bushveld Complex, South Africa - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.